Economic Performance of Cattle Fattening Business in West Lombok Regency - I Gusti Lanang Media; M. Taqiuddin; Maya Nachida; M. Prasetyo N (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
This study aims to determine: (1) how much revenue fattening Bali cattle, (2) financial feasibility of the Bali cattle fattening, and (3) channel marketing of fattening Bali cattle in West Lombok. This study was conducted over three months from Mei to Juli 2016 Month with survey methods, the number of respondents 60 people. Analysis of the data used is the analysis of input-output, BC Ratio and Return On Investment (ROI). Specifically to determine the marketing channels used descriptive analysis. The results showed that (1) The average Farmer income of fattening Bali cattle Rp.6.466.058 per person and Rp. 1.616.514 per head. (2) Bali cattle fattening shoul be developed by the BC Ratio 1,128. ROI value of Bali cattle fattening is 12,84 %, higher than prevalling bank rate is curently7,5%. (3) The farmers in West Lombok Regency majority (63%) to market its livestock fatenned animals to market, the reason is more efficient in term of time. When livestock is sold, the farmer directly to buy feeder for subsequent fattening period.